REVERSAL OF CLONIDINE-INDUCED HYPOTHERMIA BY DECAFFEINATED TEA/COFFEE EXTRACT, AND THEIR FRACTIONS IN MICE - SALVE, BALU U.; KOKARE, CHANDRAKANT R.; KASTURE, SANJAY B. (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Objective: To study the effect of decaffeinated tea extract (DTE) and decaffeinated coffee extract (DCE) and their respective fractions viz: chloroform fractions (DTCf and DCCf), ethyl acetate fractions (DTEa and DCEa), diethyl ether fractions (DTDe and DCDe) and acetone-water fractions (DTAw and DCAw) against clonidine-induced hypothermia in mice. Methods: Clonidine (0.1 mg/kg, i. p.) administered to a group of mice pretreated 30 min before with the dose of DTE or DCE or their respective fractions. Rectal temperature was measured at the time of clonidine administration and thereafter at every 30 min up to 2 h test period. Results: DTE 200 DTE 300 has significantly inhibited clonidine-induced hypothermia. Among the fractions tested, DTE fraction-DTEa 100 and 200 and DCE fractions DCDe 200 and DCAw 200 significantly (p<0.0001) reversed clonidine-induced hypothermia; the effect of DTEa was found to be more sustained. Conclusion: Both, the decaffeinated tea and coffee contain ingredients that reverse clonidine-induced hypothermia, but they are required to do so in very large doses which are not achievable with normally administered doses of decaffeinated tea or coffee.